The Effect of Work-Life Integration Practices on The Performance of Employees in Commercial Banks in Cameroon - Takemeyang, Ayuk; Ketuma, Henry Jong (International Conference on Business Management and Accounting, 2025)
The human resource is the most valuable resource of every business, and with the fast evolution of technology, Information and Communication Technology is becoming more of a necessity in every sector of business rather than an option. Also, with the high level of competition noticed in the Cameroon banking sector and the development of E-banking and other institutional setbacks facing banks and other financial institutions in Cameroon and due to the importance of employees in maximizing shareholders wealth and enhancing bank performance, the study seeks to examined the effect of work-life integration practices on the performance of employees in commercial banks in Cameroon. The study is based on the positivism epistemology and the ontology of objectivism. The study adopted a cross-sectional research design and quantitative method. A structured Questionnaire was used to collect data from a sample of 200 commercial bank employees in Cameroon. The study hypothesis was tested through the ordinary least square regression. The study result indicated that telecommuting, leave programs and fringe benefit respectively has a positive significant influence on employees’ performances. By devising human resource policies that integrate family and work practices such as more access to work from home, recovery strategies like flexible working schedules and relaxation time, and extra financial incentives, employees’ performance will increase.